2024
DOI: 10.1161/atvbaha.123.320300
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of YAP Promotor Accessibility in Endothelial Mechanotransduction

Aarren J. Mannion,
Honglei Zhao,
Yuanyuan Zhang
et al.

Abstract: BACKGROUND: Endothelial cells are constantly exposed to mechanical forces in the form of fluid shear stress, extracellular stiffness, and cyclic strain. The mechanoresponsive activity of YAP (Yes-associated protein) and its role in vascular development are well described; however, whether changes to transcription or epigenetic regulation of YAP are involved in these processes remains unanswered. Furthermore, how mechanical forces are transduced to the nucleus to drive transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Supporting this hypothesis, a recent study from our lab has shown that impairing the AmotL2 signaling axis by using short hairpin RNAs—which is phenocopied by p60AmotL2 via acting as a dominant-negative of the main isoform—leads to reduced chromatin accessibility [ 20 ]. While the mechanism of decreased chromatin accessibility in p60AMOTL2-expressing cells is not explored here, a role for perturbed cytoplasmic contractile actin filaments [ 17 ] cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this hypothesis, a recent study from our lab has shown that impairing the AmotL2 signaling axis by using short hairpin RNAs—which is phenocopied by p60AmotL2 via acting as a dominant-negative of the main isoform—leads to reduced chromatin accessibility [ 20 ]. While the mechanism of decreased chromatin accessibility in p60AMOTL2-expressing cells is not explored here, a role for perturbed cytoplasmic contractile actin filaments [ 17 ] cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…This complex initiates the formation of specific radial actin filaments connecting cellular junctions to the nuclear lamina [ 15 , 17 ]. AmotL2 has been implicated in various biological processes, including aortic development, blastocyst hatching, epithelial cell polarity, and regulation of the Hippo signaling pathway, which controls organ size and cell growth [ 12 , 17 20 ].…”
Section: Introductionmentioning
confidence: 99%